Binary approximation of random evolutions in the scheme of averaging - Svishchuk , A. V. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We consider a double approximation of semi-Markov random evolutions, namely, the averaging and diffusion approximation, when the balance condition is not fulfilled. Double approximation algorithms are applicable for reserve and transport processes and other stochastic systems in a semi-Markov random medium.